2014
DOI: 10.3390/met4030322
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical Transformation and Electrochemical Nature of Magnesium-Rich Primers during Natural Weathering

Abstract: Magnesium-rich primers (MgRP) have generated great interest as a promising alternative to chromium-based primers for the protection of aluminum substrates but their performance during exterior exposure has not been well documented. This paper focuses on the evaluation of MgRP during natural weathering to gain insight into its mineralogical phase transformation and electrochemical nature. Control studies were conducted on Mg and AA2024-T3 coupons. The results indicate that Mg particles in MgRP transform into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…As is common for outdoor exposure, and as was found in this Mg-Li study, carbonate compounds are formed and can be considered along with the usual oxide/hydroxide compounds. 2,24,30,[32][33][34][36][37][38] The stability of a carbonate compound depends on the concentration of the carbonate ion as a function of pH, as the carbonate ion can participate in proton exchange reactions according to the stability of its variously protonated species as a function of pH. 39 The total concentration of each carbonate species present as a function of pH can be calculated as expressed by Eq.…”
Section: Resultsmentioning
confidence: 99%
“…As is common for outdoor exposure, and as was found in this Mg-Li study, carbonate compounds are formed and can be considered along with the usual oxide/hydroxide compounds. 2,24,30,[32][33][34][36][37][38] The stability of a carbonate compound depends on the concentration of the carbonate ion as a function of pH, as the carbonate ion can participate in proton exchange reactions according to the stability of its variously protonated species as a function of pH. 39 The total concentration of each carbonate species present as a function of pH can be calculated as expressed by Eq.…”
Section: Resultsmentioning
confidence: 99%
“…This observation is predicting the surface becoming homogenous with the passage of exposure periods of the coating in the solution. Blucher et al (2001) and other researchers have observed that for aluminum metal exposed in NaCl solution polluted by CO 2 in the environment, the surface is inhibited by corrosion products due to the cathodic reduction of oxygen and anodic dissolution of metal by high pH [54][55][56][57]. In this study the formation of passive films that stifle the anodic dissolution of coating are as follow:…”
Section: Electrochemical Impedance Spectroscopy (Eis) Evaluation Of Cmentioning
confidence: 94%
“…1 Over the past few years, a commercial organic coating system containing a Mg-rich primer (MgRP) has been developed for the active corrosion protection of aerospace aluminum alloys. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The commercial MgRP coating system consists of a surface pretreatment, an epoxy resin with metallic Mg pigment and, where applicable, a polyurethane topcoat. The active corrosion protection of any Al alloy is provided by galvanic coupling of more active Mg pigment in the primer which is active compared to the more noble AA2024-T351 substrate.…”
mentioning
confidence: 99%